Development of a methodology for the assessment of possible responses of ecosystem services to anthropogenic activities and changes in geomorphology in the Eten coastal wetland, Lambayeque - Rojas Carbajal, Tania Victoria (2021)
Worldwide, coastal wetlands are currently threatened by human activities such as agriculture, infrastructure development, resource exploitation, and urban sprawl. Pressures on these ecosystems disturb their morphology, hydrology, and biogeochemical cycles, thus resulting in the degradation of ecosystem services quality. However, little has been done to understand the coastal wetland response to identify the most efficient conservation and mitigation strategy. Along the Peruvian coast, wetlands present a diversity of landscapes and features. Even though threats and pressures would be similar, the ecosystem response in each environment may be different. In this context, this study describes a methodology to assess the impacts of human activities on ecosystem services based on the understanding of geomorphic features and current state of the Eten coastal wetland, located in northern Peru. The methodology combines the application of open-source GIS-tools and collection of field data to characterize the geomorphic settings and the ecosystem services provided and also to analyze the changes in river morphology, land use, water quality, and aquatic biota. Data were then processed to define the main threats and pressures on the Eten wetland and how they impact on ecosystem services, using a cause-effect DSPIR (Drivers, Pressures, States, Impacts, Responses) model. The main results indicated that the river plays a vital role in defining the landscape and wetland features such as vegetation cover and habitats. Moreover, the biological diversity of aquatic habitats is disturbed by the hydraulic structures and agricultural activities. Changes in land use modified the natural landscape, thus affecting supporting and regulation services such as groundwater recharge and water regulation. By combining remote sensing applications and field surveys, this study presents an approach to improve coastal wetlands management through the identification of the most affected functions and services.